Body Fat Mass is a Strong and Negative Predictor of Peak Stimulated Growth Hormone and Bone Mineral Density in Healthy Adolescents During Transition Period - Perotti, M.; Perra, S.; Saluzzi, A.; Grassi, G.; Pincelli, A. I. (Hormone and Metabolic Research, 2013)
The adipose tissue has detrimental effects on growth hormone secretion, even in the absence of obesity. The majority of previous studies have shown an inverse relationship between fat mass and the growth hormone response to several stimulation tests in adults and in children. The contribution of body fat mass on growth hormone response to provocative tests during the transition age is not known. We analyzed the GH-IGF1 axis by GHRH-arginine test in 30 healthy adolescents with normal stature during the transition period from 14 to 18 years. All subjects underwent body composition analysis by dual-energy X-ray absorptiometry (DXA). We found that total body fat mass was inversely correlated with peak GH to provocative test (r=−0.6, p=0.004). GH deficiency was shown in 2 of our healthy patients if diagnosis was based on GH peak below 19 μg/l. Both children who failed the GHRH-arginine were overweight (BMI for age above 85th percentile). However, their GH status was normal when assessed by insulin tolerance test. Multivariate analysis demonstrated strong correlation between peak stimulated GH and measures of body adiposity, including body mass index and fat mass index, with the latter showing the most important effect on GH secretion. Fat mass index alone explained 34.5% of the variability in peak GH. This study has shown for the first time that during the transition period, GH response to GHRH-arginine test is strongly influenced by body composition, and cutoff values appropriate for overweight and obese adolescents are needed.
Keywords: GH secretion; GHRH-arginine test; obesity